Satellite formation flying : relative dynamics, formation design, fuel optimal maneuvers and formation maintenance - Wang, Danwei; Poh, Eng Kee; Wu, Baolin (Springer, 2016)
This book systematically describes the concepts and principles for multi-satellite relative motion, passive and near passive formation designs, trajectory planning and control for fuel optimal formation maneuvers, and formation flying maintenance control design. As such, it provides a sound foundation for researchers and engineers in this field to develop further theories and pursue their implementations. Though satellite formation flying is widely considered to be a major advance in space technology, there are few systematic treatments of the topic in the literature. Addressing that gap, the book offers a valuable resource for academics, researchers, postgraduate students and practitioners in the field of satellite science and engineering.
Keywords: Formation flying.; Automated vehicles.; Artificial satellites -- Tracking.; elektronické knihy; electronic books